Glass Frit Dissolution Influenced by Material Composition and the Water Content in Iodide/Triiodide Electrolyte of Dye-Sensitized Solar Cells - Katrine Flarup Jensen; Md. Mahbubur Rahman; Welmoed Veurman; Henning Brandt; Chan Im; Jürgen Wilde; Andreas Hinsch; Jae-Joon Lee (International Journal of Photoenergy)
To ensure long-term stable dye-sensitized solar cells (DSCs) and modules, a hermetic sealing is required. This research investigates the chemical stability of I-/I3- redox electrolyte and four different glass frits (GFs). Sintered GF layers were openly exposed to nonaqueous redox electrolyte and redox electrolyte with 1, 5, and 10 wt% H2O in thin, encapsulated cells. The change in I3− absorbance was assigned to a reaction between the GF and I-/I3- electrolyte and was used to evaluate the chemical stability of the different GFs. The I3− absorbance change was monitored over 100 days. Two out of the four GFs were unstable when H2O was added to the redox electrolyte. The H2O caused metal ion leaching which was determined from EDX analysis of the inorganic remains of electrolyte samples. A GF based on Bi2O3–SiO2–B2O3 with low bond strength leached bismuth into electrolyte and formed the BiI3- complex. A ZnO–SiO2–Al2O3-based GF also became unstable when H2O was added to the redox electrolyte. Leaching of zinc ions due to exchange with H+ resulted in the formation of a zinc-iodine compound which caused I3− depletion. By applying the test design to different types of GFs, the material suitability in the DSC working environment was investigated.